2010
DOI: 10.1128/aem.03095-09
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Analyses of Alexandrium catenella Cell Concentrations and Shellfish Toxicity in the Puget Sound

Abstract: Alexandrium catenella is widespread in western North America and produces a suite of potent neurotoxins that cause paralytic shellfish poisoning (PSP) in humans and have deleterious impacts on public health and economic resources. There are seasonal PSP-related closures of recreational and commercial shellfisheries in the Puget Sound, but the factors that influence cell distribution, abundance, and relationship to paralytic shellfish toxins (PSTs) in this system are poorly described. Here, a quantitative PCR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 12 publications
5
14
0
Order By: Relevance
“…Similarly, the 3-year survey in Monterey Bay noted that 20% of samples that were positive for A. catenella (abundances of Ͻ1,000 cells liter Ϫ1 ) had no measurable particulate STX (37). Similar results were obtained in Puget Sound, where almost one-third of the stations revealed no shellfish toxicity despite the presence of A. catenella in surface waters (16). The authors of the latter study concluded that the use of absolute cell numbers as an indicator of STXeq levels in shellfish was inappropriate for Puget Sound (16).…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Similarly, the 3-year survey in Monterey Bay noted that 20% of samples that were positive for A. catenella (abundances of Ͻ1,000 cells liter Ϫ1 ) had no measurable particulate STX (37). Similar results were obtained in Puget Sound, where almost one-third of the stations revealed no shellfish toxicity despite the presence of A. catenella in surface waters (16). The authors of the latter study concluded that the use of absolute cell numbers as an indicator of STXeq levels in shellfish was inappropriate for Puget Sound (16).…”
Section: Discussionsupporting
confidence: 70%
“…A. catenella cells were detected more frequently in Monterey Bay (55% of samples) (37) than in King Harbor (17% of samples). Further north, in Puget Sound, cell abundances ranged from 5 to 812,500 cells liter Ϫ1 from late April through October 2006 (16). The maximal abundances greatly exceeded the maximal abundance observed during our 4-year survey.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations